2000
DOI: 10.1099/00207713-50-2-787
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cellular fatty acids and phenotypic relationships of Agrobacterium, Bradyrhizobium, Mesorhizobium, Rhizobium and Sinorhizobium species using the Sherlock Microbial Identification System.

Abstract: Previous studies have demonstrated that cellular fatty acid analysis is a useful tool for identifying unknown strains of rhizobia and establishing taxonomic relationships between the species. In this study, the fatty acid profiles of over 600 strains belonging to the genera Agrobacterium, Bradyrhizobium, Mesorhizobium , Rhizobium and Sinorhizobium were evaluated using the gaschromatography-based Sherlock Microbial Identification System (MIS). Data collected with the MIS showed that the three phylogenetically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
122
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(150 citation statements)
references
References 28 publications
(23 reference statements)
25
122
3
Order By: Relevance
“…All the BR strains exhibited, in different proportions, C 16 : 0 , C 16 : 1 !5c and summed feature 8 (C 18 : 1 !6c/C 18 : 1 !7c) as major fatty acids; BR 446 T also presented a small amount of C 19 : 0 cyclo !8c (Table S3). These results are consistent with those found in bradyrhizobia (Tighe et al, 2000). It is noteworthy that these strains were different from B. huanghuaihaiense by having larger relative amounts of summed feature 8 and from B. arachidis by lacking C 16 : 1 !5c.…”
supporting
confidence: 82%
“…All the BR strains exhibited, in different proportions, C 16 : 0 , C 16 : 1 !5c and summed feature 8 (C 18 : 1 !6c/C 18 : 1 !7c) as major fatty acids; BR 446 T also presented a small amount of C 19 : 0 cyclo !8c (Table S3). These results are consistent with those found in bradyrhizobia (Tighe et al, 2000). It is noteworthy that these strains were different from B. huanghuaihaiense by having larger relative amounts of summed feature 8 and from B. arachidis by lacking C 16 : 1 !5c.…”
supporting
confidence: 82%
“…Fatty acid data (Jarvis et al, 1996) indicate a single cluster of species, representing Agrobacterium, Rhizobium and Sinorhizobium. With the exception of a J. M. Young quantitative difference in a single fatty acid (Tighe et al, 2000), support for Sinorhizobium as distinct from Rhizobium is on the basis of comparative 16S rDNA sequence data alone (de Lajudie et al, 1994(de Lajudie et al, , 1998b.…”
Section: International Journal Of Systematic and Evolutionary Microbimentioning
confidence: 99%
“…The cellular fatty acids were extracted, methylated (Dunfield et al, 1999), analysed by gas chromatograph and were identified using Sherlock Microbial Identification System (Tighe et al, 2000). The major cellular fatty acids (>1 %) were summed feature 8 (C 18 : 1 !6c/ C 18 : 1 !7c), C 19 : 0 cyclo !8c, summed feature 2 (C 14 : 0 3-OH/ C 16 : 1 iso/ C 12 : 0 aldehyde), C 16 : 0 , C 18 : 0 and C 17 : 0 cyclo, which were consistent with the related Ensifer species (Table S1).…”
mentioning
confidence: 99%